VOICE AND LETTERS IN CONFLICT. SOME PROBLEMS OF INTERCULTURAL PROBLEMS IN TRANSLATION - Larrú Salazar, Manuel (2013)
Any compendium of linguistic expression that is passed into writing is faced with the kind of problem that is related to its oral nature since this cannot be verified in the same manner, also there is the problem of the constantly changing nature of such expression. As well as the problem of oral speech there is another that has to do with the translation and even the very possibility of translation, something that is very clear when one looks at texts written in Quechua for example. When the translators manipulate a story ideologically they not only alter the system of the original language but even its basic symbols and sometimes they even end up repressing the Quechua text in its direct forms of representation and finally lose sight of a cosmovision that they will find difficult to recover.